JUSTIFICATION OF CONTROL SYSTEM TYPES OF UNMANNED AERIAL VEHICLE FOR CIVIL AVIATION - Kharchenko, Volodymyr; Мatiychyk, Denys (Proceedings of National Aviation University (archive), 2017)
Objective: The problem of unmanned aerial vehicle control systems is a complicated issue which requires consideration of the tasks and applications of unmanned aerial vehicles. The typology of control systems combination for civil unmanned aerial vehicle is suggested and justified. Methods: The methodology of the research was based on application of the varieties of the experts method for rationale of the variants of control system combinations for a specific type of unmanned aerial vehicle and the morphological analysis was used to generate the variants of control system combinations. Results: The causes that lead to discrepancies in types of control systems for civil unmanned aerial vehicle are revealed. Compliance between remote radio control application and type of feedback signal are considered. Based on morphological analysis method, 25 variants of combined unmanned aerial vehicle control systems are suggested. Discussion: Regulatory, substantive and technical components of basic unmanned aerial vehicle control systems are considered. The practical experience of the development by Scientific Production Center of Unmanned Aviation “Virazh” is used to demonstrate the applicability of findings.